Study Of Code Division Multiple Access (CDMA) Technique For Mobile Communication Systems - Sainel, Sairee (Universiti Sains Malaysia, 2005)
This report presents details study of CDMA technique for mobile communication systems. The objective of this project is to understand the spread spectrum techniques including DS-CDMA and also to explain IS-95A system. The test results for simulation on the IS-95A Reverse traffic channel are included to evaluate the performance of the channel under various traffic conditions. Various conditions are applied to the system to decide on the best performance. The performance of the channel was measured in terms of BER. Reasonable Doppler shift frequency is determined. It is found that performance of the system vary with the reduced of data rate. Amount of AWGN added to the signal represents the interference generated by other base station nearer. Therefore changes of SNR in the AWGN Channel provoke the system performance. The detection performance improves with an increase in the SNR.